2004
DOI: 10.1136/thorax.2003.013888
|View full text |Cite
|
Sign up to set email alerts
|

Local activation of coagulation and inhibition of fibrinolysis in the lung during ventilator associated pneumonia

Abstract: Background: Fibrin deposition is a hallmark of pneumonia. To determine the kinetics of alterations in local coagulation and fibrinolysis in relation to ventilator associated pneumonia (VAP), a single centre prospective study of serial changes in pulmonary and systemic thrombin generation and fibrinolytic activity was conducted in patients at risk for VAP. Methods: Non-directed bronchial lavage (NBL) was performed on alternate days in patients expected to require mechanical ventilation for more than 5 days. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 19 publications
(32 reference statements)
7
127
1
Order By: Relevance
“…Earlier it has been demonstrated that pulmonary coagulopathy is an important feature of pulmonary infection (38,39), with changes in fibrin generation being restricted to the site of infection in patients with community-acquired pneumonia caused by S. pneumoniae (46) or ventilator-associated pneumonia caused by several pathogens, among others P. aeruginosa (47,48). Pulmonary coagulopathy now gains more and more interest as a new target in therapeutic studies of acute lung injury of pneumonia (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier it has been demonstrated that pulmonary coagulopathy is an important feature of pulmonary infection (38,39), with changes in fibrin generation being restricted to the site of infection in patients with community-acquired pneumonia caused by S. pneumoniae (46) or ventilator-associated pneumonia caused by several pathogens, among others P. aeruginosa (47,48). Pulmonary coagulopathy now gains more and more interest as a new target in therapeutic studies of acute lung injury of pneumonia (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Ontology analysis of the candidate genes demonstrates that the major mechanical stretch-related ALI biological process was blood coagulation with genes in this ontology including fibrinogen A, coagulation factor III, plasminogen activator, urokinase receptor (uPAR), tissue factor, and PAI-1 ( Figure 3). Many of these same genes have been implicated elsewhere as potential candidate genes in ALI (13,28,29) and in VALI (30,31). In addition to coagulation, there was prominent representation of genes involved in innate immunity (MIF, CD14, TNF, IL-1RA, C5aR, IL-6).…”
Section: Cross-species Gene Expression Profiling and Identification Omentioning
confidence: 96%
“…Depressed fibrinolytic activity is related to high pulmonary concentrations of the main inhibitor of fibrinolysis in lung tissue, plasminogen activator inhibitor type 1 (PAI-1). The importance of the fibrinolytic system in the pathogenesis of pneumonia is underscored by the observation that a depression of bronchoalveolar fibrinolysis precedes the clinical occurrence of pneumonia by several days (7). Bronchoalveolar fluid levels of PAI-1 are increased in burn patients with inhalation trauma and in patients with ARDS (12,31) and is probably secreted by lung epithelial cells, fibroblasts, and endothelial cells (32,33).…”
Section: Fibrinolysismentioning
confidence: 99%
“…In association with enhanced fibrin production, fibrinolytic activity is depressed in alveolar fluids of patients with pneumonia (7,20,22), patients with inhalation trauma (12), and patients with ARDS (6). Depressed fibrinolytic activity is related to high pulmonary concentrations of the main inhibitor of fibrinolysis in lung tissue, plasminogen activator inhibitor type 1 (PAI-1).…”
Section: Fibrinolysismentioning
confidence: 99%
See 1 more Smart Citation